Answer:
LM = 24.3
Step-by-step explanation:
In terms of similar shapes, we know that the ratio of the value of one side to its corresponding side value is equal to another. In other words, we know that LK and HG are corresponding sides by looking at the quadrilaterals. The ratio of LK to HG is equal to the ratio of another pair of corresponding sides, such as LM and IH.
Therefore, the ratio of LK and HG (LK/HG) is equal to the ratio of LM and IH (LM/IH) . Make sure to keep the same quadrilateral's sides on top/bottom. In this example, LM and LK are on the same quadrilateral, and are therefore both on top. Similarly, IH and HG are of the same quadrilateral and are both on bottom. We can write this as
LK / HG = LM / IH
34/7 = LM / 5
Multiply both sides by 5
34*5/7 = LM
LM ≈ 24.2857
Rounding to the nearest tenth, LM = 24.3
Answer:
24.3
Step-by-step explanation:
2r x s
for r = 2 and s = 4.
Answer:
16
Step-by-step explanation:
2rs
Let r=2 and s=4
2*2*4
4*4
16
{2, 4, 6, 8...} ...} f(1) = 2 and f(n) = f(n - 1) + 2 for n >
{12, 14, 16, 18...} f(1) = 12 and f(n) = f(n - 1) + 2 for n > 1
Given:
To find:
The sequence and recursive expression to the given explicit expression.
Solution:
We have,
For n=1,
The value of f(1) is 12.
Similarly,
For n=2,
For n=3,
For n=4,
The required sequence is {12,14,16,18,...}.
The recursive expression of an AP is
where, d is common difference.
Here d=2,
Therefore, the recursive expression is .
Answer:
I'm assuming you mean the negative number of it so -12
Step-by-step explanation:
Answer:
-12 miles
Step-by-step explanation:
below is a key word, so you know you are going down
n = 2
n = fraction 5 over 3
n = fraction 5 over 2
Answer:
n = 2
Step-by-step explanation:
3/5n - 4/5 = 1/5n
3/5(2) - 4/5 = 1/5(2)
6/5 - 4/5 = 2/5
^^^^^^^^^^^^^^^^
Correct? Yes.
Answer:
The equation of the line is y = x + 1
Step-by-step explanation:
The equation of the line is y = m x + b, where
The rule of the slope of the line is m = , where
∵ The line passes through points (3, 4) and (-4, -3)
∴ x1 = 3 and y1 = 4
∴ x2 = -4 and y = -3
→ Substitute them in the rule of the slope above to find it
∵ m = = = 1
∴ m = 1
→ Substitute it in the form of the equation above
∴ y = 1(x) + b
∴ y = x + b
→ To find b substitute x by 3 and y by 4 in the equation
∵ 4 = 3 + b
→ Subtract 3 from both sides
∵ 4 - 3 = 3 - 3 + b
∴ 1 = b
→ Substitute it in the equation
∴ y = x + 1
∴ The equation of the line is y = x + 1